Jødisk aktivisme i Danmark 1938-1943 - Arnheim, Arthur (Rambam. Tidsskrift for jødisk kultur og forskning, 2021)
As part of “The Final Solution” the Germans planned to arrest and deport all Jews in Denmark on the 1st of October 1943. It is well known that the Danish people protected and rescued the majority of the Jewish population. While the Jewish leadership and the individual Jews in Denmark were passive during the rescue operation, one Jewish family was active in the effort to save their fellow Jews. This article is about the Sompolinsky family. Shimshon and Dora Sompolinsky came from Poland and settled in Copenhagen in 1914. They raised nine children, and in 1931 the family obtained Danish citizenship. After finishing high school, their son Meir Sompolinsky was in 1938 sent to Palestine on a scholarship to study education. In 1940 when the Germans occupied Denmark, Meir Sompolinsky found himself isolated without contact to family or community. At the end of September 1943 rumors reached Palestine about the German attack on the Danish Jews. At that time the British mandatory government maintained restrictions on Jewish immigration to Palestine. Meir Sompolinsky knew, however, that a small quota of “Certificates” (visas) had been arranged for leading Jews and Zionists. Meir Sompolinsky made a list of 87 Jewish families in Denmark which he forwarded to the Jewish Agency. He also made contact with the International Red Cross in order to obtain assistance with the protection and transportation of Jews to Palestine. The plan reached the foreign office in London on the 30th of October. By that time all Danish Jews were either in Sweden or in Theresienstadt. Meir Sompolinsky’s younger brother David had in the meantime been active in Copenhagen in an extraordinary effort to help his fellow Jews. Three days after the first warning about a German attack was received, neither the Jews nor the Danish public were prepared. David Sompolinsky, on the other hand, had analyzed the situation in detail and was ready to act. David Sompolinsky approached hospitals in order to request that Jews be admitted as patients under false names. He mobilized the teachers of his old high school. They together formed the Lyngby Group which eventually brought 700 Jews to safety in Sweden. David Sompolinsky approached the prison authorities and demanded the release of all Jewish prisoners before the Germans would get to them. His last deed before seeking safety in Sweden was to personally escort Jewish children who had been hidden in an asylum for children to Sweden. The motivation behind David Sompolinsky’s activities becomes evident by tracing his life story. He settled in Israel in 1950 and became professor in the field of microbiology. In 1960 he took part in an Israeli rescue operation in the former Belgian colony of Congo. The moral compass which has directed David Sompolinsky’s life is the Jewish code of conduct called Halacha. One halachic law takes preference over all other laws: The duty to save human lives.